2022
DOI: 10.7717/peerj.14062
|View full text |Cite
|
Sign up to set email alerts
|

miR-378 associated with proliferation, migration and apoptosis properties in A549 cells and targeted NPNT in COPD

Abstract: Background microRNAs contribute to the development and progression of chronic obstructive pulmonary disease (COPD). However, the underlying molecular mechanisms are largely unclear. The goal of this study was to investigate the roles of miR-378 in alveolar epithelial type II cells and identify molecular mechanisms which contribute to the pathogenesis of COPD. Materials and methods Human alveolar epithelial (A549) cells were cultured in Dulbecco’s Modified Eagle Medium. Cell proliferation was studied by using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…It has been reported that telomerase is overexpressed in 85–90% of cancer cells, whereas HeLa cells have high expression of miR378, 36 and miR378 is overexpressed in non-small cell lung cancer. 29 However, in MDA-MB-231 cells, as the invasion and migration increased, miR-378 was virtually absent. 37 The results showed that DTP could enter cancer cells to detect the different expressions levels of miR378 and telomerase in cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that telomerase is overexpressed in 85–90% of cancer cells, whereas HeLa cells have high expression of miR378, 36 and miR378 is overexpressed in non-small cell lung cancer. 29 However, in MDA-MB-231 cells, as the invasion and migration increased, miR-378 was virtually absent. 37 The results showed that DTP could enter cancer cells to detect the different expressions levels of miR378 and telomerase in cells.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that miR378 is upregulated in cervical cancer tissues and A549 cells, which significantly promotes the proliferation and migration of cancer cells and inhibits cell apoptosis, so it plays an important role in the pathogenesis of cervical cancer and non-small cell lung cancer. 28,29 Therefore, telomerase was selected as a broad-spectrum tumor marker, combined with disease-specific tumor marker miR378 to ensure the accurate diagnosis of cancers.…”
Section: Introductionmentioning
confidence: 99%